Cognitive limitations and biases in risk decisions - Austin, Laurel C. (Henry Stewart Talks, 2012)
Defining risk, Risk decision biases, Risk decision heuristics, Perceptions of cancer clusters, Intuitive risk perceptions, Representativeness heuristic, Errors in risk decisions, Representativeness bias, Confirmation bias, Thinking about base rates, Fallacy of the 'law' of small numbers, Overconfidence bias, Invulnerability bias, Gambler's fallacy, Belief in the hot hand, Seeing patterns in random events, Texas sharpshooter fallacy, Implications for businesses, Developing a culture of risk, Instilling a culture of managing risk